Comparative analysis on the damage properties of the Ili loess under dry–wet and freeze–thaw cycles - Zhang, Zizhao; Hu, Yang; Lv, Qianli; Hao, Ruihua; Tang, Guobin (Frontiers in Earth Science, 2025)
The structural integrity of slopes in the Ili Valley is critically influenced by the inherent characteristics of loess, particularly when it is subjected to the seasonal climatic changes. In the present research, a series of triaxial shear tests were carried out to examine the mechanical behavior of the Ili loess under different dry–wet and frost–thaw cycles. In parallel, some testing methods, including scanning electron microscopy (SEM) and nuclear magnetic resonance (NMR), were applied to investigate the progressive damage characteristics and the alterations in terms of the microstructures. Test results demonstrated a strong correlation between the macroscopic mechanical resistance and microstructural changes of the Ili loess subjected to the dry–wet and freeze–thaw cycles. The impact of the freeze–thaw cycles was more pronounced than other parameters, when the reduction in shear strength of the Ili loess under dry–wet cycles was accounted for. The results also showed that either the cohesion or the internal friction angle is very different from each other. Furthermore, changes in terms of the microstructure, such as the particle size, porosity, morphology, soil structure, and particle contact mode, exhibited distinct characteristics under varying climates. The research outcomes obtained from this research offer valuable data reference and theoretical guidelines to prevent or postpone the occurrence of the landslide in the Ili Valley under critical environmental conditions.